Inverse association between serum free thyroxine levels and hepatic steatosis: results from the Study of Health in Pomerania - Ittermann, Till; Haring, Robin; Wallaschofski, Henri; Baumeister, Sebastian E; Nauck, Matthias; Dörr, Marcus; Lerch, Markus M; Lerch, Markus; Meyer zu Schwabedissen, Henriette E; Rosskopf, Dieter; Völzke, Henry (Thyroid (New York, N.Y.), 2012)
Associations between thyroid function and hepatic steatosis defined by enzymatic and sonographic criteria are largely unknown in the general population. Thus, the aim of the present study was to investigate the association between thyroid function tests and sonographic as well as enzymatic criteria of liver status in a large population-based study, the Study of Health in Germany (SHIP). Data from 3661 SHIP participants without a self-reported history of thyroid or liver disease were analyzed. Hepatic steatosis was defined as the presence of a hyperechogenic ultrasound pattern of the liver and increased serum alanine transferase concentrations. Serum thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) concentrations were associated with hepatic steatosis using multinomial regression models adjusted for sex, age, physical activity, alcohol consumption, waist circumference, and food intake pattern. We detected no consistent association of serum TSH and FT3 concentrations with hepatic steatosis. In contrast, serum FT4 concentrations were inversely associated with hepatic steatosis in men (odds ratio (OR)=0.04 [95% confidence interval (CI)=0.01; 0.17]) and women (OR=0.06 [95% CI=0.01; 0.42]). Results from the present cross-sectional study suggest that low FT4 concentrations are associated with hepatic steatosis. Longitudinal and intervention studies are warranted to investigate whether hypothyroidism increases the risk of hepatic steatosis or vice versa.